If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -16 + 2q = 4q Solving -16 + 2q = 4q Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '-4q' to each side of the equation. -16 + 2q + -4q = 4q + -4q Combine like terms: 2q + -4q = -2q -16 + -2q = 4q + -4q Combine like terms: 4q + -4q = 0 -16 + -2q = 0 Add '16' to each side of the equation. -16 + 16 + -2q = 0 + 16 Combine like terms: -16 + 16 = 0 0 + -2q = 0 + 16 -2q = 0 + 16 Combine like terms: 0 + 16 = 16 -2q = 16 Divide each side by '-2'. q = -8 Simplifying q = -8
| (x^2)(x^2)= | | 1x-15r= | | -9(x+3)+4x+5=8x+12 | | 2/3×-15r= | | 32=x^2-1 | | f(x)=9x^2-4 | | (x^2+3)(x^2+4x-3)= | | (a+1)+(a+b)I=-2+5i | | -5t+7=11t-4 | | -2(6q+4)+4(q-6)= | | e^5/2e | | 14x-6x=-24 | | 15x^2-16x+1= | | 9x+8=7x+56 | | 156=28-y | | (a-1/2)(a-1/5)= | | 21+7(x-3)=6x+1 | | 5x-3=10x+2 | | 5t-3=11 | | (7a+7)(6a+5)= | | 2y+2.6=7.8 | | 32x+15=4(7x-12) | | 16(6x-1)-4=94x+16 | | 28n-8+5n= | | 7(x-1)=4x-25 | | 6x+5+7=0 | | 7x+12=4x-1+3x | | -6x+4=-4x-12 | | 4=x(x/2) | | 195x^2+89x-84=0 | | 9x^4-30x^3+24x^2=0 | | 5/6/1/4=x |